A New Model for Formation of Lacustrine Primary Dolomite by Subaqueous Hydrothermal Venting. Issue 6 (18th March 2021) - Yang, Zhe; Whitaker, Fiona F.; Liu, Runchao; Phillips, Jeremy C.; Zhong, Dakang
Abstract: Almost 230 years after it was first described, formation of the mineral dolomite remains enigmatic. Dolomitic rocks are abundant throughout the geological record, and most are thought to form by replacement of limestone. Recent work has identified substantial volumes of high‐temperature primary dolomite deposited in Cretaceous lacustrine rift basins in Northern China. Here we provide the missing conceptual understanding of the fundamental processes that may have formed such dolomitic sediments by combining an analysis of the physics and chemistry of sub‐lacustrine hydrothermal systems with new data on the mineralogy and geochemistry of the dolomites. This novel mechanism accounts for systematic changes in the characteristics of the dolomite sequence that intimately link with the evolution of convection within the fault damage zone and venting of brine‐rich mixtures to the lake basin, and provides a new model to be tested against dolomitic sediments in high‐enthalpy settings such as rifting basins. Plain Language Summary: Dolomite is a common constituent of much of the sedimentary record, a host for hydrocarbons and ore minerals, and has attracted immense research interest as an indicator of carbon and magnesium cycles, paleoclimate and the chemical history of seawater. However, modern dolomites are rare in earth surface environment and the processes governing dolomite formation are an actively debated topic of current research. Herein, we show for the first time how high‐temperature dolomite can precipitate directly from subaqueous cooling layers of vented hydrothermal fluids within sufficient time. Our innovative model is based on physical and chemical calculations and supported by geological observations and isotopic measurements. This model has wider relevance for the formation of dolomite in high heat‐flux settings including rift basins worldwide, and provide a new eye to inspect problem of dolomite formation. Key Points: High‐temperature primary dolomites can be precipitated rapidly in free suspension from hydrothermal fluids vented into the base of a lake The evolution of hydrothermal convection in fault damage zone causes systematic changes in the characteristics of the dolomite sequence The new model for high‐temperature primary dolomites in high‐enthalpy settings provides a motivation for viewing the origin of dolomites